Penerapan Sistem Informasi Manajemen dalam Pengelolaan Pendidikan di SMA Negeri 1 Semarang (Jurnal Sosial Humaniora dan Pendidikan, 2025)
The rapid advancement of information technology has significantly transformed educational management, prompting schools to adopt integrated systems for administrative efficiency and decision-making. This study explores the implementation of Management Information Systems (MIS) in the educational context, with a particular focus on SMA Negeri 1 Semarang, Indonesia. The study aims to examine the definitions, objectives, and benefits of MIS as applied in school operations, and to analyze how systems such as DAPODIK, ARKAS, and the School Report Card contribute to improving school performance. Using a qualitative descriptive method and a case study approach, data were collected through document analysis and literature review. The findings reveal that MIS supports various aspects of school management, including student and teacher data management, financial planning, curriculum monitoring, and performance evaluation. These systems have improved data accuracy, enhanced transparency, and strengthened accountability in school administration. The study concludes that MIS implementation in SMA Negeri 1 Semarang has led to more effective, responsive, and evidence-based educational governance. The paper recommends continuous capacity building for school staff, regular evaluation, and the development of supportive infrastructure to maximize the impact of MIS in schools across Indonesia.